Relationship between nonformal education and Islamic Education in the Context of 2045 Agenda towards Education 4.0 and Society 5.0: Bibliometric Analysis - Elihami Elihami (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2022)
This study discusses relationship between nonformal education and Islamic education  in the context of 2045 agenda towards education 4.0 and society 5.0. The research aimed to relate nonformal education (95 papers) and Islamic Education (990 papers) through the period of 1958- 2022. The VOSviewer application is used to analyse the retrieved bibliographic citation data. The performance of the most productive authors, journals, keywords, and citation references is examined. The rate of relative growth and the time required to double have been calculated. In the years 1958- 2022. The results of the study found how to act so that nonformal education and Islamic Education learning can acclimatize education 4.0 with compacted steps to reach society 5.0. The research novelty showed that there was the addition of new literature about nonformal education and Islamic Education through bibliometric analysis and there was variation